High-Frequency Ultrasound of Multiple Arterial Areas Reveals Increased Intima Media Thickness, Vessel Wall Appearance, and Atherosclerotic Plaques in Systemic Lupus Erythematosus - Svensson, Christina; Eriksson, Per; Zachrisson, Helene; Sjöwall, Christopher (Frontiers in Medicine, 2020)
Introduction: Patients with systemic lupus erythematosus (SLE) still have increased risks of cerebro- and cardiovascular disease (CVD). High-frequency ultrasound (US) provides an opportunity to distinguish atherosclerosis from inflammation in the vessels. We hypothesised that an extended US protocol could add information regarding vascular affection in SLE. Methods: 60 patients (52 women, 8 men; mean age 43.2±11.3 years) with SLE characterised by either lupus nephritis (LN; n=20), antiphospholipid syndrome (APS; n=20) or skin & joint involvement (n=20) and matched healthy controls (n=60) were included. Intima-media thickness (IMT), assessment of vessel walls, and plaque occurrence were recorded using high-frequency US (GE Logic E9) in common carotid, internal carotid, brachiocephalic, subclavian, axillary, common femoral, and proximal superficial femoral arteries as well as in the aortic arch. Results: For the entire SLE group, IMT was increased in the internal carotid artery (0.52±0.17 vs 0.45±0.09 mm, p=0.004), the common femoral artery (0.57±0.23 vs. 0.49±0.11 mm, p<0.01), the subclavian artery (0.58±0.19 vs. 0.53±0.13 mm, p=0.02) and the aortic arch (1.21±0.63 vs. 0.98±0.25 mm, p=0.002) compared to controls. These differences were primarily observed in the APS and the LN group compared to controls. Vessels with increased IMT ≥0.9 mm had a smooth, medium echogenic appearance in areas free of atherosclerotic plaques. Atherosclerotic plaques were detected in 15/60 patients (25%) compared to 2/60 controls (3%). Plaques were predominantly (67%) located in the carotid bifurcation. Multivariate analysis revealed influence of age on IMT in all vessel areas. Furthermore, in common femoral artery, sagittal abdominal diameter, diastolic blood pressure and cholesterol showed association. In internal carotid artery, male sex and presence of Raynaud influenced IMT. Conclusion: Among SLE cases without the presence of plaques, an extended US protocol revealed increased wall thickness with predominantly medium echogenic appearance highlighting possibly inflammation or early atherosclerosis. The appearance of the vessel walls has not previously been studied in detail. An increased number of plaques was found in SLE compared to age- and sex-matched healthy controls. We found similar risk factors for increased IMT and occurrence of plaques indicating atherosclerotic mechanisms rather than inflammation.